Significant short-term shifts in the microbiomes of smokers with periodontitis after periodontal therapy with amoxicillin & metronidazole as revealed by 16S rDNA amplicon next generation sequencing - Hagenfeld, Daniel; Matern, Johannes; Prior, Karola; Harks, Inga; Eickholz, Peter; Lorenz, Katrin; Kim, Ti-Sun; Kocher, Thomas; Meyle, Jörg; Kaner, Doğan; Schlagenhauf, Ulrich; Harmsen, Dag; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
The aim was, to compare the effects of mechanical periodontal therapy with or without adjunctive amoxicillin and metronidazole on the subgingival microbiome of smokers with periodontitis using 16S rDNA amplicon next generation sequencing. Fifty-four periodontitis patients that smoke received either non-surgical periodontal therapy with adjunctive Amoxicillin and Metronidazole (n = 27) or with placebos (n = 27). Subgingival plaque samples were taken before and two months after therapy. Bacterial genomic DNA was isolated and the V4 hypervariable region of the bacterial 16S rRNA genes was amplified. Up to 96 libraries were normalized and pooled for Illumina MiSeq paired-end sequencing with almost fully overlapping 250 base pairs reads. Exact ribosomal sequence variants (RSVs) were inferred with DADA2. Microbial diversity and changes on the genus and RSV level were analyzed with non-parametric tests and a negative binomial regression model, respectively. Before therapy, the demographic, clinical, and microbial parameters were not significantly different between the placebo and antibiotic groups. Two months after the therapy, clinical parameters improved and there was a significantly increased dissimilarity of microbiomes between the two groups. In the antibiotic group, there was a significant reduction of genera classified as Porphyromonas, Tannerella, and Treponema, and 22 other genera also decreased significantly, while Selenomonas, Capnocytophaga, Actinomycetes, and five other genera significantly increased. In the placebo group, however, there was not a significant decrease in periodontal pathogens after therapy and only five other genera decreased, while Veillonella and nine other genera increased. We conclude that in periodontitis patients who smoke, microbial shifts occurred two months after periodontal therapy with either antibiotics or placebo, but genera including periodontal pathogens decreased significantly only with adjunctive antibiotics.